Neuroimmunoendocrine dysfunctions in case of bacterial purulent meningitis in children - L. A. Alekseeva; T. V. Bessonova; A. A. Zhirkov; A. A. Vilnits; G. F. Zheleznikova; K. V. Zhdanov (Журнал инфектологии)
Objective: to study neuroimmunoendocrine dysfunctions in children with bacterial purulent meningitis and to determine their value in the character of the disease course and outcomes.Materials and methods. 56 children hospitalized to Pediatric Research and Clinical Center for Infectious Diseases with the diagnosis of bacterial purulent meningitis were examined. Besides standard clinical, biochemical and hemostasis tests there were studied concentration of cytokines by xMAP technology; A, M, and G immunoglobulins – by quantitative immunoturbodimetric method; cortisol, neurospecific proteins – by immune-enzyme test; blood subpopulations of lymphocytes – by flow cytofluorimetry method.Results. Different changes of laboratory indicators characterizing neuroimmunoendocrine dysfunctions dependent on severity of the course and outcome of bacterial purulent meningitis were identified. Children with more severe course of the disease during its acute period had a reliable increase of S-100 protein in blood serum, concentration of granulocytic colony-stimulating, and concentration of BВ subunit produced by growth factor platelets was decreased. In case of the formation of expressed neurologic consequences within the disease outcome, higher concentration of neurospecific enolase, relative content of natural killers, and lower concentration of monocytic chemoattractant protein 1 were identified during the period of reconvalescence in comparison with a favorable neurologic outcome.Conclusion. The results of the study give evidence of the possibility of more accurate early prognosis of the disease course and outcome on the basis of evaluation of neuroimmunoendocrine dysfunctions and this is extremely important to determine therapy management during both acute and reconvalescence periods of bacterial purulent meningitis.